HPLC analysis of biomarkers of Toluene and Xylene in human urine samples - Maurya, Pawan Kumar; Yadav, Anupa; Maurya, Pankaj (International Journal of Occupational Safety and Health, 2023)
Introduction: Urinary Hippuric acid (HA) and Methylhippuric acid (MHA) are considered reliable biomarkers for monitoring exposure to toluene and xylenes. A simple and robust HPLC method for simultaneous determination of HA and MHA in urine samples was developed and validated as per Internation Conference on Harmonization (ICH) Q2 guidelines. Methods: Mobile phase consisting of two solvents A & B, solvent A was 0.1% TFA in water, and solvent B was 0.1% TFA in acetonitrile. Separation was performed in gradient elution mode and the time program was as follows - Time (min)/%B: 0/20, 4/20, 11/80, 11.1/90, 16/90, 16.1/20, 25/20. The detection wavelength was 205 nm. Results: The limits of detection (LOD) and quantification (LOQ) of HA in urine were 0.3 and 1.0 mg/L, and for MHA were 0.25 mg/L and 1.0 mg/L respectively and the recovery for HA and MHA were 95% and 98.9% respectively. Conclusion: The developed method was successfully applied for the analysis of urine samples.